Debulking surgery in advanced melanoma. Issue 11 (November 2011) - Gajdos, Csaba; McCarter, Martin D
In general, patients with stage IV melanoma have poor survival. However, there are subsets of stage IV melanoma patients who are candidates for surgical debulking. There is a growing body of retrospective evidence about clinicians being able to better select patients who may benefit from surgical resection in isolated stage IV disease. In addition, palliative-type resections may improve quality of life in selected cases. In this article, we discuss how recent advances in effective systemic therapies for melanoma may impact the clinical use of debulking surgery in melanoma patients. We also review the available literature about the rationale, risks, benefits and selection of patients for these procedures.